Cultural Acculturation: The Process of Migrating and Fundamentals of Batak-Melayu Culture in Kisaran, Asahan Regency - Margolang, Dinda Pratiwi; Syam, Abdi Mubarak (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The topic of this paper is about Cultural Acculturation. The main reason this research was raised because in Kisaran, Asahan Regency, there has been a cultural acculturation between the Toba Batak and Malay. The Toba Batak tribe located in Toba Regency is a migrant tribe that has entered the lowlands of the east coast, especially in Asahan Regency which is rich in agricultural and plantation resources. Cultural diversity between the Batak and Malay tribes occurred in Asahan when the Batak people migrated to the Malay lands. This study explains First, how the process of Batak-Malay cultural acculturation occurred in Kisaran. Second, it explains the Migration and Integration of Batak culture into Malay culture in Kisaran Asahan. Third, the forms of Cultural Acculturation between Batak and Malay. The method used in this study is Qualitative with a Historical approach. The location of the research was carried out around the Kisaran city area, Asahan Regency. Data was obtained through an in-depth interview process involving informants, community leaders, religious leaders and academics. Then other data is strengthened from reputable books and journals related to the topic being studied. This study found that in Kisaran, Asahan Regency, there has been a Cultural Acculturation where the Batak people have carried out traditions and customs from the Malays. The acculturation between these two cultures gave birth to a Malay culture that has characteristics that are different from the Malay culture in the archipelago. The Malays in this city have traits and characteristics that tend to be rough and tough, like the character of the Toba Batak ethnic group.